2020
DOI: 10.1111/1471-0528.16261
|View full text |Cite
|
Sign up to set email alerts
|

Effect of progestogen for women with threatened miscarriage: a systematic review and meta‐analysis

Abstract: Conclusion Progestogens may have benefits on live birth rate and miscarriage rate for women with threatened miscarriage. These benefits appear to be confined to the use of oral progestogen, and no statistically significant improvements were seen with vaginal progesterone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 24 publications
0
13
0
4
Order By: Relevance
“…We thank Di Renzo and Fonseca for their letter 1 and interest in our study. 2 They question the inclusion of a trial of oral dydrogesterone included in our analysis which they feel was of low quality, and which was not included in a previous Cochrane systematic review.…”
Section: Sirmentioning
confidence: 97%
See 1 more Smart Citation
“…We thank Di Renzo and Fonseca for their letter 1 and interest in our study. 2 They question the inclusion of a trial of oral dydrogesterone included in our analysis which they feel was of low quality, and which was not included in a previous Cochrane systematic review.…”
Section: Sirmentioning
confidence: 97%
“…We read with great interest, the article by Illingworth et al titled 'Evaluation of treatments for Bartholin's cyst or abscess: a systematic review'. 1 The article was particularly relevant owing to the fact that Bartholin's abscess is a common gynaecological presentation that we encounter regularly in clinical practice. Although this article provided some insight into the various techniques for managing Bartholin's abscess around the world, 1 there are a few points that we would like to raise.…”
Section: Referencesmentioning
confidence: 99%
“…We agree with Devall et al that highquality, randomised trials are needed to assess the safety and efficacy of oral progestogens and that current evidence is insufficient to allow us to draw solid conclusions about the safety of dydrogesterone use in early pregnancy. & Sir, Findings about the effect of progestogens in threatened miscarriage in the work by Li et al 1 are welcome and appreciated. The condition has a profound impact, as the affected women suffer the threat of pregnancy loss.…”
Section: Sirmentioning
confidence: 98%
“…Sir, We thank Di Renzo and Fonseca for their letter 1 and interest in our study. 2 They question the inclusion of a trial of oral dydrogesterone included in our analysis which they feel was of low quality, and which was not included in a previous Cochrane systematic review.…”
Section: Authors' Replymentioning
confidence: 98%
“…The efficacy of progestogen therapy has been studied in women with threatened miscarriage and a history of recurrent miscarriage. Previous systematic reviews and meta-analyses have synthesized the literature and have suggested a potential benefit from progesterone therapy, especially for the subgroup of women with a history of three or more miscarriages [ 4 7 ]. The ACOG (American College of Obstetricians and Gynecologists) clinical management guidelines have concluded, “use of progestins for threatened early pregnancy loss is controversial, and conclusive evidence supporting their use is lacking.…”
Section: Introductionmentioning
confidence: 99%